International tourism and export instability. - Sinclair, M. Thea (1990)
Concludes that international tourism can provide a rapidly growing source of foreign exchange which both industrialised and developing countries are increasingly keen to tap. However, rather than offsetting the instability of earnings from more traditional merchandise exports, receipts from travel can amplify net export earnings instability in some developing economies.